2016
DOI: 10.2174/1574891x11666161024165304
|View full text |Cite
|
Sign up to set email alerts
|

Targets and Patented Drugs for Chemotherapy of Chagas Disease in the Last 15 Years-Period

Abstract: In summary, loans on anti-Chagas disease agents focused to specific parasite targets as their metabolic pathways or specific enzymes will be summarized. Targets will also be specifically discussed. Patent literature collected and published from 2000 to 2015, alleging inhibitors for specific T. cruzi targets or trypanocidal activity was achieved over the search database from Delphion Research intellectual property network including international patents and the European patent office, Espacenet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 603 publications
(716 reference statements)
0
18
0
Order By: Relevance
“…The current drugs available to treat the infection, benznidazol (Bnz) and nifurtimox have several drawbacks such as (i) high toxicity which causes severe side effects [4]; (ii) their lack of efficacy in the treatment of the chronic stage of infection [5]; and (iii) poor medical infrastructure: less than 1% of infected people have access to diagnostics and treatment [65]. Therefore, there is a need for new therapeutic strategies, safer and affordable drugs and validated drug-targets against Chagas disease [6,7]. Indeed, many T. cruzi enzymes and processes have been proposed as drug targets [7], including the trypanothione-dependent antioxidant pathway [[8], [9], [10], [11]].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current drugs available to treat the infection, benznidazol (Bnz) and nifurtimox have several drawbacks such as (i) high toxicity which causes severe side effects [4]; (ii) their lack of efficacy in the treatment of the chronic stage of infection [5]; and (iii) poor medical infrastructure: less than 1% of infected people have access to diagnostics and treatment [65]. Therefore, there is a need for new therapeutic strategies, safer and affordable drugs and validated drug-targets against Chagas disease [6,7]. Indeed, many T. cruzi enzymes and processes have been proposed as drug targets [7], including the trypanothione-dependent antioxidant pathway [[8], [9], [10], [11]].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need for new therapeutic strategies, safer and affordable drugs and validated drug-targets against Chagas disease [6,7]. Indeed, many T. cruzi enzymes and processes have been proposed as drug targets [7], including the trypanothione-dependent antioxidant pathway [[8], [9], [10], [11]].…”
Section: Introductionmentioning
confidence: 99%
“…The activity of the immune system induced by 4-Cl is substantial; however, 4-Cl is considered a hybrid molecule, and the presence of two or more mechanisms of action for this molecule is not surprising. Therefore, the investigation of other possible targets inside T. cruzi is recommended (28). Since thiosemicarbazones are known to inhibit the T. cruzi protease cruzain, an enzyme that has essential functions for parasite survival as discussed above, a molecular docking simulation was performed with this enzyme to identify its possible role as a target of 4-Cl in the parasite.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro tests performed by our research group with thiazide derivatives aryl thiosemicarbazones and aryl-4-thiazolinones showed that they had an effective anti-T. cruzi activity (Donnici et al, 2009) even on a nanomolar scale as confirmed by the high affinity of these molecules for cruzain during docking studies. The most potent and well-known inhibitor of this enzyme is K777 ( Figure 1G ), which is about to enter clinical studies (McKerrow et al, 2009; Duschak, 2016). In the same way as for trans-sialidase, a screening with drugs that were approved by the FDA was conducted for cruzain and found that four compounds could be used as a basis to design new drugs, namely etofylline clofibrate (antilipemic, Figure 1H ) and piperacillin, cefoperazone, and flucloxacillin (antibiotics, Figures 1I–K , respectively) (Palos et al, 2017).…”
Section: Synthetic Drugs and New Therapeutic Approaches For Chagas DImentioning
confidence: 99%